Lowered ADCP data during RV MARIA S. MERIAN cruise MSM121 - Leimann, Ilmar; Mertens, Christian (PANGAEA, 2025)
LADCP measurements used a two-instrument configuration with two Teledyne RDI 300 kHz workhorse ADCPs mounted in down- and up-looking positions. Data collection and processing was performed according to recommendations in the GO-SHIP manual (Thurnherr et al., 2010).
Keywords: currents; LADCP; North Atlantic